Value oriented developmental interaction capability: A driver for teamwork performance - Endang Sulistiyani; Augusty Tae Ferdinand (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
The objective of this research is to develop a conceptual model, by proposing the concept of value oriented developmental interaction capability, to fill in the research gap between knowledge sharing and team performance among the functional teams in the organization, then testing the model in the hotel industries in Yogyakarta Special Region and Central Java Province in Indonesia. Adopting the interaction theory and the concept of work values, the concept of value oriented developmental interaction capability is introduced and inserted in the research model for mediating the influence of knowledge sharing to teamwork performance. A purposive sampling is adopted in inviting employee in a hospitality industry sector to participate in this research. Following the acceptance of the regression coefficients, the Sobel test statistics is conducted and proving the role of value oriented developmental interaction capability as a mediator between knowledge sharing and teamwork performance.
Keywords: D23; D83; L88; O34; 650; knowledge sharing; value oriented developmental interaction capability; teamwork efficacy; teamwork performance; work value; Indonesia